2013
DOI: 10.1007/s12028-013-9819-0
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion Increases the Risk of Thrombotic Events in Patients with Subarachnoid Hemorrhage

Abstract: RBCT is associated with an increased risk of TE and VTE in SAH patients. A dose-dependent relationship exists between number of units transfused and thrombosis. Age of blood does not appear to play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…These considerations continue to challenge clinicians to balance the risks and benefits of treating anaemia with transfusions, and have led to controversies on whether transfusion should be administered to anaemic patients in the absence of compelling clinical reasons, such as severe symptoms or haemodynamic instability. RBC transfusions have been associated with increased mortality and poor outcomes in patients with subarachnoid haemorrhage due to increased risk of thrombotic events . Conversely, administering RBC transfusions to patients with ischaemic stroke did not worsen their prognosis, although the treatment was associated with longer duration of mechanical ventilation and length of stay in intensive care units .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These considerations continue to challenge clinicians to balance the risks and benefits of treating anaemia with transfusions, and have led to controversies on whether transfusion should be administered to anaemic patients in the absence of compelling clinical reasons, such as severe symptoms or haemodynamic instability. RBC transfusions have been associated with increased mortality and poor outcomes in patients with subarachnoid haemorrhage due to increased risk of thrombotic events . Conversely, administering RBC transfusions to patients with ischaemic stroke did not worsen their prognosis, although the treatment was associated with longer duration of mechanical ventilation and length of stay in intensive care units .…”
Section: Discussionmentioning
confidence: 98%
“…Anaemia is associated with higher morbidity and mortality in patients with acute and chronic cardiopulmonary diseases, including acute myocardial infarction, heart failure, pneumonia and COPD . Treating anaemia with red blood cell (RBC) transfusion after acute myocardial infarction, congestive heart failure and ischaemic stroke is controversial and has been linked with adverse outcomes . Acute pulmonary embolism (PE) is the third leading cause of cardiovascular death after coronary artery disease and stroke .…”
Section: Introductionmentioning
confidence: 99%
“…10,31 Three studies assessing the frequent use of transfusion in patients with subarachnoid hemorrhage suggested that transfusion was associated with worse outcomes, including greater risk for vasospasm, thrombotic events, and death. 23,25,35 However, a small randomized trial in patients with subarachnoid hemorrhage found that maintaining higher hemoglobin levels via transfusion may be safe and feasible. 28 A recent systematic review of neurocritically ill patients concluded that sufficient evidence does not exist to allow distinction between the efficacy of a lower or higher threshold of transfusion in these patients.…”
Section: Interpretation Of Results In the Context Of The Literaturementioning
confidence: 99%
“…The impact of transfusions cannot be excluded as a risk factor for VTE, too. Kumar et al [13] presented a relationship between the red blood transfusion and an increased risk of VTE in neurological patients (with subarachnoid haemorrhage). A dose-dependent association exists between the number of units transfused and thrombosis, the age of blood does not appear to play a role.…”
Section: Discussionmentioning
confidence: 99%